Telaah Pergeseran Paradigma Asas dan Prinsip Dalam Pendirian Perusahaan Pasca Undang-Undang Cipta Kerja: Tinjauan Konsep dan Penerapannya Terhadap Perusahaan Perorangan - Jessica Fionita; Ariawan Gunadi (UNES Law Review, 2023)
Establishing a single person limited company is a concept for establishing a company that emerged after the Job Creation Law was passed. Single person limited company allow a company to be established with only one person. This is of course regarding the debate regarding shifting the paradigm regarding the principles and concepts of responsibility that have been adhered to in the corporate legal regime. In this research, the author aims to examine the concept of establishment and responsibility for the formation of single person limited companies after the enactment of the Job Creation Law. This research is normative legal research using conceptual and statutory approaches. In fact, the paradigm shift from the concept of a capital partnership which can be established by a single shareholder is not something new because this has been explained in Article 7 paragraph (5) of the Limited Liability Company Law which states that a company can be established with only one shareholder entity such as an entity. State-Owned Enterprises (BUMN). Single person limited Companies that provide flexibility to shareholders to create a company that can be established by a single shareholder provided that it meets the existing criteria for Small and Medium Enterprises (UMK). The liability of this single person limited company remains the same as that of a Limited Liability Company which has liability limited to the shares owned by the shareholder as explained in article 153 J paragraph (2) of the Job Creation Law as long as there are no matters excluded in that article.